2012
DOI: 10.4269/ajtmh.2012.11-0626
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Entamoeba histolytica Infection in China

Abstract: Abstract. The seroprevalence of Entamoeba histolytica infection in the residents of seven provinces in China was examined by using an enzyme-linked immunosorbent assay with a crude antigen and a recombinant surface antigen, C-Igl, of the parasites. A total of 1,312 serum samples were investigated. The positivity rates for these two antigens were 11.05% and 6.25%, respectively. There was no significant difference in the seropositivity to E. histolytica between men and women. We used a logistic regression model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Seropositivities in all age groups were higher in our study areas compared with the Chinese population, in which seropositivities ranged from 3–8% [36]. Comparing the seropositivities among children from our two study sites, the rates for children from Mbita were generally higher than those for children from Kwale.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Seropositivities in all age groups were higher in our study areas compared with the Chinese population, in which seropositivities ranged from 3–8% [36]. Comparing the seropositivities among children from our two study sites, the rates for children from Mbita were generally higher than those for children from Kwale.…”
Section: Discussionmentioning
confidence: 46%
“…For the assay for E. histolytica , the recombinant surface antigen C-IgL was previously validated [12] and was used for seroepidemiology of E. histolytica in Chinese populations [36]. Seropositivities in all age groups were higher in our study areas compared with the Chinese population, in which seropositivities ranged from 3–8% [36].…”
Section: Discussionmentioning
confidence: 89%
“…Brief Report survey of HIV-positive patients in China showed a serum-positive rate of 7.9% for E. histolytica (4). A recent study in seven provinces in China has shown a serum-positive rate of 0.53% to 9.04% for E. histolytica (5). However, insufficient pathogenic information on Chinese E. histolytica strains is currently available.…”
Section: Discussionmentioning
confidence: 99%
“…The trophozoites (2 × 10 4 ) were incubated with 10 5 Jurkat cells (The Cell Bank of Chinese Academy of Science, Shanghai, China) for 20 min at 37°C. The cells were then washed twice and stained with FITCconjugated annexin V (Sigma-Aldrich).…”
Section: Apoptosis In Jurkat Cellsmentioning
confidence: 99%
“…In Japan, invasive amebiasis is an emerging sexually transmitted parasitic disease, increasing alongside the incidence rates of other sexually transmitted infections (STIs) including human immunodeficiency virus (HIV), chlamydial, and gonococcal infections 14,15. Previous studies have indicated that HIV infection is a risk factor for invasive amebiasis 11,13,16,17. However, epidemiological data on the trends of invasive amebiasis in patients with and without HIV infection are scarce.…”
Section: Introductionmentioning
confidence: 99%